2021
DOI: 10.3390/molecules26216356
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Betulin Derivatives Containing Thio-/Semicarbazone Moieties as Apoptotic Inducers through Mitochindria-Related Pathways

Abstract: Two new series of betulin derivatives with semicarbazone (7a–g) or thiosemicarbazone (8a–g) groups at the C-28 position were synthesized. All compounds were evaluated for their in vitro cytotoxicities in human hepatocellular carcinoma cells (HepG2), human breast carcinoma cells (MCF-7), human lung carcinoma cells (A549), human colorectal cells (HCT-116) and normal human gastric epithelial cells (GES-1). Among these compounds, 8f displayed the most potent cytotoxicity with an IC50 value of 5.86 ± 0.61 μM agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…In contrast, in an experiment conducted by Wang et al [ 79 ], betulin derivatives containing a thio/-semicabazone group showed low cytotoxic activity against colon cancer cells of the HCT-116 line. Interestingly, only the obtained derivative lup-20(29)-ene-3β-ol-28-N-((3-trifluoromethyl-4-chloro)phenyl)semicarbazide 20g displayed significant cytotoxic activity against the CRC line [ 79 ].…”
Section: Effects Of Betulin and Its Derivatives On Gastrointestinal T...mentioning
confidence: 85%
See 2 more Smart Citations
“…In contrast, in an experiment conducted by Wang et al [ 79 ], betulin derivatives containing a thio/-semicabazone group showed low cytotoxic activity against colon cancer cells of the HCT-116 line. Interestingly, only the obtained derivative lup-20(29)-ene-3β-ol-28-N-((3-trifluoromethyl-4-chloro)phenyl)semicarbazide 20g displayed significant cytotoxic activity against the CRC line [ 79 ].…”
Section: Effects Of Betulin and Its Derivatives On Gastrointestinal T...mentioning
confidence: 85%
“…Studies of the cytotoxic effect on HCT-116 cells conducted for this group of derivatives showed that the hydrazide and hydrazine derivatives containing a 4-trifluoromethylphenyl substituent ( 22d and 23h ) were the most active (IC 50 equal to 13.70 and 12.55 μM). Derivatives containing the pyridine ring 22i (IC 50 = 9.30 μM) and 23k (IC 50 = 9.32 μM) had the strongest effects on human hepatocellular carcinoma cells (HepG2) [ 79 , 80 , 81 ].…”
Section: Synthesis Of Betulin Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Betulin ( Figure 1 ), pentacyclic lupane-structure triterpenoid which occurs abundantly in the birch bark, is one such compound since it has been shown to inhibit growth and migration as well as induce apoptosis of various types of cancer cells. Moreover, betulin can been utilized as a precursor compound for the synthesis of novel derivatives with improved pharmacological properties and potential use in cancer treatment [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Covalently bonded networks of POPs are utilized in various biomedical applications because of their cell penetration compatibility, cell viability, and large-scale synthesis facilities [ 26 , 27 , 28 ]. Anticancer activity studies have been carried out on a colorectal carcinoma cell line (HCT 116), where these porous nanomaterials act as cell destroyer or drug delivery systems [ 29 , 30 , 31 ]. Functionalized POP materials having small particle sizes mean they are effective for target-specific cell death.…”
Section: Introductionmentioning
confidence: 99%